Heat Treatment of Aluminum Alloys with the Natural Combination of Dopants - Tsepeleva, Alisa; Novák, Pavel; Kolesnichenko, Evdokim; Michalcová, Alena; Kačenka, Zdeněk; Kubásek, Jiří (Materials (Basel, Switzerland), 2022)
Aluminothermic reduction without the separation of individual metals is currently considered as a possible method for processing ferromanganese sea nodules and creating new alloys. In this study, the product of their reduction-a manganese-based polymetallic mixture-was added to pure aluminum, as a mixture of alloying elements in their natural ratios. After extrusion, two new aluminum alloys with a total percentage of metallic additives ranging from 1 to 6 percent were prepared. The possibilities of the precipitation strengthening of these aluminum alloys, especially those containing Mn, Fe, Si, Ni, and Cu, were investigated under a wide range of heat treatment conditions. After each tested combination of annealing and artificial aging temperatures, the phase composition and the microstructure changes were recorded by X-ray diffraction, optical, and scanning electron microscopy with EDS analysis. Under none of the tested heat treatment conditions is a significant hardening effect observed, even though the precipitate phases are observed by TEM. However, the changes in the morphology of the present intermetallic phases caused by the heat treatment are revealed, which highlights the further possible development of these multicomponent alloys.
Keywords: heat treatment; aluminum alloys; ferromanganese sea nodules